The right to inclusive education for children with visual impairments in primary schools of Zimbabwe - Nyamutswa, Mercy Tsitsi (Midlands State University, 2019)
This study ventures into the right to inclusive education for children with visual impairments in primary schools of Zimbabwe. This will be done to establish whether or not Zimbabwe is in conformity with the international standards set by the Convention on the Rights of Persons with Disabilities (CRPD) to which Zimbabwe is a party. The study explores the international and regional frameworks on the right to education. The study further explores the national framework of Zimbabwe on the right to education and juxtaposes it with the CRPD to establish whether Zimbabwe is in conformity with international standards. In addition, the study provides a situational analysis of Zimbabwe and South Africa on the right to inclusive education for children with visual impairments in primary schools to expose the gaps in the education system of Zimbabwe and to show that on the other hand, South Africa has the best laws and policies on inclusive education to cater for children with visual impairments in primary schools. Lastly, the writer outlines the findings and conclusions of the study and proceeds to proffer recommendations.